The postcolonial museum the arts of memory and the pressures of history - Chambers, Iain 1949-; De Angelis, Alessandra 1975-; Ianniciello, Celeste; Orabona, Mariangela; Quadraro, Michaela (Routledge, Taylor & Francis Group, 2016)
Introduction : disruptive encounters. museums, arts, and postcoloniality / Alessandra De Angelis, Celeste Ianniciello, Mariangela Orabona, Michaela Quadraro -- A museum without objects / Françoise Vergès -- Decolonizing national museums of ethnography in Europe : exposing and reshaping colonial heritage (2000-2012) / Felicity Bodenstein and Camilla Pagani -- Colonial spaces, postcolonial narratives : the exhibitionary landscape of Fort Cochin in India / Neelima Jeychandran -- Ethnographic museums : from colonial exposition to intercultural dialogue / Fabienne Boursiquot -- "There is not yet a world" / Ebadur Rahman -- The artist as interlocutor and the labour of memory / Joanna Figiel, Mihaela Brebenel, Christopher Collier -- Performance in the museum space (for a wandering society) / Margherita Parati -- "Museo diffuso" : performing memory in public spaces / Viviana Gravano -- Mining the museum in an age of migration / Anne Ring Petersen -- Blurring history : the Central European museum and the schizophrenia of capital / Ivan Jurica -- The limits to institutional change : organisational roles and roots / Peggy Levitt -- The incurable image : curation and repetition on a tri-continental scene / Tarek Elhaik -- The postcolonial "exhibitionary complex" : the role of the international expo in migrating and multicultural societies / Stefania Zuliani -- Orientalism and the politics of contemporary art exhibitions / Alessandra Marino -- What museum for Africa? / Itala Vivan -- Egyptian chemistry : from post-colonial to post-humanist matters / Ursula Biemann -- "The lived moment" : new aesthetics for migrant recollection / Peter Leese -- Coding/decoding the archive / David Gauthier and Erin La Cour -- Afterword : after the museum / Iain Chambers